Motivating learning disabled offenders with alcohol-related problems: a pilot study. - Mendel E; Hipkins J (British Journal of Learning Disabilities, 2002)
The present study aimed to apply motivational interviewing techniques in assisting clients with learning disabilities through the Stages of Change (Prochaska & Diclemente 1986). Motivational interviewing and the stages of change model have been effectively applied to alcohol problems. However, this approach has not been applied to people with learning disabilities. Particularly within a forensic service, there is a need to develop group treatments for people with alcohol-related offences as current alcohol education programmes do not necessarily lead to changes in attitudes and behaviour. This involved interactive teaching methods adapted for people with mild learning disabilities. The group met for 1 h over three sessions and staff training was provided. A variety of measures (pre and post group) demonstrated increases in clients' motivation, self-efficacy and determination to change their drinking behaviour. Recommendations were made to develop the group further.